2016
DOI: 10.1364/ol.41.000472
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution magnetic field imaging with a nitrogen-vacancy diamond sensor integrated with a photonic-crystal fiber

Abstract: We demonstrate high-resolution magnetic field imaging with a scanning fiber-optic probe which couples nitrogen-vacancy (NV) centers in diamond to a high-numerical-aperture photonic-crystal fiber integrated with a two-wire microwave transmission line. Magnetic resonance excitation of NV centers driven by the microwave field is read out through optical interrogation through the photonic-crystal fiber to enable high-speed, high-sensitivity magnetic field imaging with sub 30 μm spatial resolution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…However, the depth over which the NV centres are coupled to the fibre is of the order of w/θ where w is the radius at 1/e2 of the fibre mode. Owing to the large mode radius (2.35 μm) and the small value of θ, the resulting coupling depth is 28 μm, which shows the advantage of using a thick sample and compares well with experiments based on diamond microcrystals . The useful volume of the sample can thus be estimated to w3/θ.…”
Section: Resultssupporting
confidence: 62%
See 1 more Smart Citation
“…However, the depth over which the NV centres are coupled to the fibre is of the order of w/θ where w is the radius at 1/e2 of the fibre mode. Owing to the large mode radius (2.35 μm) and the small value of θ, the resulting coupling depth is 28 μm, which shows the advantage of using a thick sample and compares well with experiments based on diamond microcrystals . The useful volume of the sample can thus be estimated to w3/θ.…”
Section: Resultssupporting
confidence: 62%
“…By combining a diamond microcrystal coupled to a 200 μm core diameter optical fibre. Fedotov et al recently built a compact magnetometer based on a similar structure. To improve the sensitivity of this kind of device, high quality bulk diamond crystals synthesised by means of chemical vapour deposition (CVD) process could be used instead of diamond microcrystals since their synthesis is now well mastered but also because intrinsic NV centres exhibit generally far better spin coherence properties.…”
Section: Introductionmentioning
confidence: 99%
“…The 2D magnetic field was imaged by the probe, using the photoluminescence spin-readout return from the NV centers. [288][289][290][291] In addition to advancements concerning the complexity of fiber tip electrode structures, high performance all-in-fiber devices, such as modulators, phototransistors, and Hall magnetic field sensors, will be developed in the future.…”
Section: Optical Modulationmentioning
confidence: 99%
“…Nevertheless, the sophistication and lack of portability of such high-end microscopes has led to interest in integrating diamond NV centers with glass optical fibers. To date, the most commonly used approach to realize such a hybrid device relies on growing or placing diamond materials external to the fiber, [11][12][13][14] which enables NV emitters to locate either on the endface of the fiber [15][16][17] or tapered fiber regions. [18][19][20] Diamond nanoparticles have been combined with tellurite (Te) glass to create hybrid diamond-glass fibers, [21] and Mayani et al demonstrated distributed diamond-fiber magnetometry by periodically spacing photodiode chips along a polycarbonate cladding to detect the diamond-microfluidic systems configurated in a hollow-core silica fiber.…”
Section: Introductionmentioning
confidence: 99%